Analysis of the Fergana Ethnic Conflict - Bekmirzaev Rakhmonali Begalievich (Genius Journals, 2023)
This article describes the details of the ethnic conflict that took place in 1989 in the Fergana region between the local people and the Turko-Meskhetian people.
Keywords: USSR; Fergana valley; 1989 Fergana massacre